Digital Health: Is it the future for our lives? - Giannoulakis, Alexandros (Health & Research Journal, 2022)
Digital health is a revolution and it includes many different opportunities, in order to improve the patients’ quality of life in hospital and at homes. The digital health technologies include telehealth, mHealth applications, data analytics, remote patient monitoring. The benefits for patients, insurance companies and healthcare providers are many and one of the most important is a time and cost saving and the aggregation of data. The future leading healthcare system must be established on a framework, which include understanding of law, patients, who need these services, the appropriate technology (safe network for data aggregation, equipment), peer support systems and sustainability.